EXPRESSION OF cDNA FOR MARINE ANNELID METALLOPROTEIN IN ESCHERICHIA COLI (Sciences & Technologie. C, Biotechnologies, 2002)
A cDNA library of Nereis diversicolor coelomocytes was constructed in expression vector λgt 11. Selection of clones of recombined phages was performed using the immunoreactivity of an anti-metalloprotein (anti-MPII) polyclonal antibody. It is of importance to note that this selection was confirmed with the use of two anti-MPII monoclonal antibodies. Conditions for strong expression of fusion proteins by bacteria which had integrated the recombined phages, and conditions for detection of these proteins by host cells. Nevertheless, it must be mentioned that these proteins, though altered, retained their antibacterial activity.